2017
DOI: 10.1038/nm.4338
|View full text |Cite
|
Sign up to set email alerts
|

A role for oncostatin M in inflammatory bowel disease

Abstract: A new study identifies oncostatin M (OSM) as a potential biomarker and therapeutic target for anti-tumor necrosis factor (TNF)-refractory inflammatory bowel disease (IBD), and pinpoints mucosal stromal cells as key players in OSM-mediated inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
(14 reference statements)
3
16
0
Order By: Relevance
“…These predictions agreed with previous studies implicating IL1A and IL1B, TNF, IFNG, NFκB, CSF2, and TGFB in pediatric IBD [26,27]. Also, OSM has been implicated in adult IBD patients [28][29][30]. It is important to note that the upstream regulators were predicted based on their known effects on downstream groups of genes.…”
Section: Identification Of Pathways and Upstream Regulators Insupporting
confidence: 88%
“…These predictions agreed with previous studies implicating IL1A and IL1B, TNF, IFNG, NFκB, CSF2, and TGFB in pediatric IBD [26,27]. Also, OSM has been implicated in adult IBD patients [28][29][30]. It is important to note that the upstream regulators were predicted based on their known effects on downstream groups of genes.…”
Section: Identification Of Pathways and Upstream Regulators Insupporting
confidence: 88%
“…As OSM has been suggested to have a progressive effect in chronic inflammatory diseases such as, RA[54] and inflammatory bowel disease[36,55], it has been proposed as a possible pharmaceutical target to suppress inflammation in these diseases[36,54,55] and the effect of anti-OSM treatment in RA has already been investigated in a phase 2 clinical trial[54]. However, considering the anti-atherogenic effects and positive effect of OSM on survival in the present study, we strongly recommend that cardiovascular disease markers and survival are carefully monitored when testing an OSM inhibiting approach.…”
Section: Discussionmentioning
confidence: 99%
“…A recent interesting study showed the cytokine oncostatin M (OSM) to be highly upregulated in inflamed mucosal tissue of IBD patients [ 115 ]. The OSM receptor (OSMR) is expressed by nonhematopoietic and nonepithelial intestinal stromal cells, which respond to OSM by producing various pro-inflammatory molecules, including IL-6, the leukocyte adhesion factor ICAM1, and chemokines that attract neutrophils, monocytes, and T-cells [ 116 ]. However, in a counter regulatory mechanism, OSM promotes epithelial repair during inflammation [ 117 ].…”
Section: Cytokine Regulation In Intestinal Pathologymentioning
confidence: 99%